The Political Development Cycle: The Right and the Left in People’s Republic of China from 1953 - Cheremukhin, Anton; Golosov, Mikhail; Guriev, Sergei; Tsyvinski, Aleh (American Economic Review, 2024)
We quantify the effects of the political development cycle—the fluctuations between the Left (Maoist) and the Right (pragmatist) development policies—on growth and structural transformation of China in 1953–1978. The left policies prioritized structural transformation toward nonagricultural production and consumption at the expense of agricultural development. The right policies prioritized agricultural consumption through slower structural transformation. The imperfect implementation of these policies led to large welfare costs of the political development cycle in a distorted economy undergoing a structural change. (JEL D72, N15, N45, N55, O21, P21, P24)